The Paths to Connectedness: A Review of the Antecedents of Connectedness to Nature - Lengieza, Michael L.; Swim, Janet K. (Frontiers in Psychology, 2021)
Abstract Although many philosophers and environmental psychologists agree that progress toward a more ecologically conscious society depends upon individuals developing a sense of connectedness to nature, such agreement is of limited use if we do not understand how connectedness forms. The purpose of this review is to delineate the state of the psychological literature concerning the antecedents of connectedness to nature. The literature review is organized into three main sections: (1) situational contexts that influence connectedness; (2) individual difference predictors, such as demographic group membership, personality, or beliefs; and (3) internal psychological states that may explain psychological processes that result in connectedness. Major critiques of the extant literature and future directions are presented in a discussion following the body of the review. The primary implications highlighted by the review are a greater need for theories delineating the formation of connectedness, a greater focus on process, and increased differentiation between similar antecedents of connectedness. Keywords: Connectedness to Nature, Contact with Nature, Self, Antecedents, Literature Review.